Fibroblast growth factor 23 is independently associated with renal magnesium handling in patients with chronic kidney disease - Grigore, Teodora V.; Zuidscherwoude, Malou; Witasp, Anna; Barany, Peter; Wernerson, Annika; Bruchfeld, Annette; Xu, Hong; Olauson, Hannes; Hoenderop, Joost (Frontiers in Endocrinology, 2023)
Background Disturbances in magnesium homeostasis are common in patients with chronic kidney disease (CKD) and are associated with increased mortality. The kidney is a key organ in maintaining normal serum magnesium concentrations. To this end, fractional excretion of magnesium (FEMg) increases as renal function declines. Despite recent progress, the hormonal regulation of renal magnesium handling is incompletely understood. Fibroblast Growth Factor 23 (FGF23) is a phosphaturic hormone that has been linked to renal magnesium handling. However, it has not yet been reported whether FGF23 is associated to renal magnesium handling in CKD patients. Methods The associations between plasma FGF23 levels, plasma and urine magnesium concentrations and FEMg was investigated in a cohort of 198 non-dialysis CKD patients undergoing renal biopsy. Results FGF23 was significantly correlated with FEMg (Pearson’s correlation coefficient = 0.37, p<0.001) and urinary magnesium (-0.14, p=0.04), but not with plasma magnesium. The association between FGF23 and FEMg remained significant after adjusting for potential confounders, including eGFR, parathyroid hormone and 25-hydroxyvitamin D. Conclusions We report that plasma FGF23 is independently associated to measures of renal magnesium handling in a cohort of non-dialysis CKD patients. A potential causal relationship should be investigated in future studies.